Recurrent structural variation, clustered sites of selection, and disease risk for the complement factor H ( CFH ) gene family - Stuart Cantsilieris; Bradley J. Nelson; John Huddleston; Carl Baker; Lana Harshman; Kelsi Penewit; Katherine M. Munson; Melanie Sorensen; AnneMarie E. Welch; Vy Dang; Felix Graßmann; Andrea J. Richardson; et al. (2018)
Significance Genetic variation of the complement factor H ( CFH ) gene family is associated with several complex diseases. Here, we have performed both long- and short-read sequencing of multiple humans and nonhuman primates in an effort to understand its complex evolutionary history. We find that this locus has evolved predominantly through incomplete segmental duplication and identify recurrent reuse of donor and acceptor duplications leading to CFHR fusion genes with diverse functions. Investigation of a large cohort of patients with age-related macular degeneration revealed multiple structural variation breakpoints and mutational burdens that cluster in specific domains of the CFH protein. These domains overlap sites showing signatures of natural selection, providing strong evidence for the shared role of selective pressure on diversity and disease.